Hyperspectral imaging for food quality analysis and control - Sun, Da-Wen (Academic, 2010)
Based on the integration of computer vision and spectrscopy techniques, hyperspectral imaging is a novel technology for obtaining both spatial and spectral information on a product. Used for nearly 20 years in the aerospace and military industries, more recently hyperspectral imaging has emerged and matured into one of the most powerful and rapidly growing methods of non-destructive food quality analysis and control. Hyperspectral Imaging for Food Quality Analysis and Control provides the core information about how this proven science can be practically applied for food quality assessment, including information on the equipment available and selection of the most appropriate of those instruments. Additionally, real-world food-industry-based examples are included, giving the reader important insights into the actual application of the science in evaluating food products. *Presentation of principles and instruments provides core understanding of how this science performs, as well as guideline on selecting the most appropriate equipment for implementation *Includes real-world, practical application to demonstrate the viability and challenges of working with this technology *Provides necessary information for making correct determination on use of hyperspectral imaging.
Keywords: Food adulteration and inspection.; Food -- Quality.; Imaging systems.; elektronické knihy; electronic books